Experimental investigation of structural failure during the cooling phase of a fire: Concrete columns. (December 2022) - Gernay, Thomas; Franssen, Jean-Marc; Robert, Fabienne; McNamee, Robert; Felicetti, Roberto; Bamonte, Patrick; Brunkhorst, Sven; Mohaine, Siyimane; Zehfuß, Jochen
Abstract: Structures may collapse during the cooling phase of a fire, yet standard furnace tests only measure the response under heating. There lacks experimental test protocols and design methods to assess resistance until burnout. This paper describes a new experimental approach for burnout resistance evaluation, reports experimental data on loaded reinforced concrete columns in furnace tests with cooling down phases, and presents numerical models of the tests. The test results show that columns designed for a standard fire resistance of 60 min exhibited a fire resistance of 83 min in the furnace but failed during the cooling phase when the burners were shut off after 72 min while the load was maintained. Two other specimens survived exposure to heating of 45 and 55 min, respectively, and their residual capacity was measured. Finite element analyses show agreement with the tests, showing applicability of numerical methods for evaluating burnout resistance of concrete columns. These findings demonstrate experimentally that delayed thermal-mechanical effects can jeopardize structural stability in real fires, and provide a framework to measure these effects. Moving beyond fire resistance to quantify the response until burnout will support designs for safety of occupants and firefighters throughout the fire and promote repairability and resilience.